Kinetics of the hydrolysis of cocoa pod shell CCN-51: Consideraciones sobre la influencia de la temperatura. - Sanchez Quezada, Johanna Patricia; Soler Herrero, Jaime; Herguido, Javier (Jornada de Jóvenes Investigadores del I3A, 2019)
The kinetics of the hydrolysis of the shell of the cocoa pod has been developed, keeping the biomass and mineral acid loads constant and varying temperature and time of operation. The behavior in the production of fermentable sugars is valued, the values of the degradation products being considerable as negligible.